2022
DOI: 10.3390/children9050670
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adolescent Idiopathic Scoliosis on Axial Rotation of the Spine: A Study of Twisting Using Surface Topography

Abstract: Axial twisting of the spine has been previously shown to be affected by scoliosis with decreased motion and asymmetric twisting. Existing methods for evaluating twisting may be cumbersome, unreliable, or require radiation exposure. In this study, we present an automated surface topographic measurement tool to evaluate global axial rotation of the spine, along with two measurements: twisting range of motion (TROM) and twisting asymmetry index (TASI). The aim of this study is to evaluate the impact of scoliosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Recent studies utilizing this system have shown a noteworthy distinction in axial motion between individuals with and without scoliosis. The research findings further indicate significant differences, both in cases of severe scoliosis compared to the control group and in cases of thoracic scoliosis compared to controls [58]. Another study conducted using the same system reveals that patients with severe structural deformity and restricted range of motion do not exhibit a decrease in their physical activity level, as indicated by validated patient activity questionnaires [59].…”
Section: State Of the Art Developmentsmentioning
confidence: 68%
“…Recent studies utilizing this system have shown a noteworthy distinction in axial motion between individuals with and without scoliosis. The research findings further indicate significant differences, both in cases of severe scoliosis compared to the control group and in cases of thoracic scoliosis compared to controls [58]. Another study conducted using the same system reveals that patients with severe structural deformity and restricted range of motion do not exhibit a decrease in their physical activity level, as indicated by validated patient activity questionnaires [59].…”
Section: State Of the Art Developmentsmentioning
confidence: 68%
“…1C), shoulder volume asymmetry, centroid lateral displacement (Fig. 1B); range of motion (ROM) measures were also included: 10 coronal angle ROM, forward sagittal angle, C7 twisting ROM, C7 twisting asymmetry index (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated reliability for assessing deformity, symmetry, and range of motion for IS, [9][10][11] and may be useful in objectively assessing a patient's deformity and its association with pain. A previous study identified that Scoliosis Research Society (SRS)-22r mental health and self-image domains correlate poorly with surface topographical measures of deformity; 12 however, the pain domain was not assessed.…”
mentioning
confidence: 99%
See 1 more Smart Citation